Comparison of Reproductive Function Between Normal and Hyperandrogenemia Conditions in Female Mice With Deletion of Hepatic Androgen Receptor - Feng, Mingxiao; Divall, Sara; Jones, Dustin; Ubba, Vaibhave; Fu, Xiaomin; Yang, Ling; Wang, Hong; Yang, Xiaofeng; Wu, Sheng (Frontiers in Endocrinology, 2022)
Obesity, altered glucose homeostasis, hyperinsulinism, and reproductive dysfunction develops in female humans and mammals with hyperandrogenism. We previously reported that low dose dihydrotestosterone (DHT) administration results in metabolic and reproductive dysfunction in the absence of obesity in female mice, and conditional knock-out of the androgen receptor (Ar) in the liver (LivARKO) protects female mice from DHT-induced glucose intolerance and hyperinsulinemia. Since altered metabolic function will regulate reproduction, and liver plays a pivotal role in the reversible regulation of reproductive function, we sought to determine the reproductive phenotype of LivARKO mice under normal and hyperandrogenemic conditions. Using Cre/Lox technology, we deleted the Ar in the liver, and we observed LivARKO female mice have normal puberty timing, cyclicity and reproductive function. After DHT treatment, like control mice, LivARKO experience altered estrous cycling, reduced numbers of corpus lutea, and infertility. Liver Ar is not involved in hyperandrogenemia-induced reproductive dysfunction. The reproductive dysfunction in the DHT-treated LivARKO lean females with normal glucose homeostasis indicates that androgen-induced reproductive dysfunction is independent from metabolic dysfunction.